Jogos em Grafos de Ações e Equilíbrios de Nash - Daniel Prado Mendes de Mello (2014)
This work addresses an important area of mathematics: The Game Theory, whose focus is the analysis of how to model phenomena that can be observed when two or more decision agents interacting always seeking to optimize their decisions. We will focus on the development of algorithms and implementations computational for solving problems involving game theory, focusing on Nash equilibria in zero sum games. The topics of game theory will be covered only from an expository way, no matter the proof of theorems.